(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Throughout this article, we present locally prime, locally primary and locally S-semiprime submodules, as generalizations of prime, primary and semiprime submodules respectively. We investigate some properties and characterizations of these modules. For a multiplication module, the concepts of locally primary and locally primary are equivalent. Finally, we give the following result, if is multiplication module, then is locally primary submodule, if there exists a locally primary ideal of such that and . We provided that, every locally semiprime submodule of multiplication module is the intersection of some locally prime submodule.